On the associativity property of MPF over M16 - Mihalkovich, Aleksejus (Lietuvos matematikos rinkinys, 2018)
The objective of this paper is to find suitable non-commuting algebraic structure to be used as a platform structure in the so-called matrix power function (MPF). We think it is non-trivial and interesting problem could be useful for candidate one-way function (OWF) construction with application in cryptography. Since the cornerstone of OWF construction using non-commuting algebraic structures is the satisfiability of certain associativity conditions, we consider one of the possible choices, i.e. the group M16, explore its basic properties and construct templates to use in our future work.
Keywords: matrix power function (MPF); one-way function (OWF); non-commuting algebraic structures